(untitled) - Rubino, Joe (Canada, 2006)
The principles, strategies, and tactics presented in this book will help you maximize your personal effectiveness, attitude, and behavior as you build your dynasty on a solid foundation that will ensure it will last long into the future. Based on proven, time-tested strategies and the long experience of two well-known and extremely well-qualified authors, this book is an indispensable tool for every network marketer, even those just starting out.
Keywords: Multilevel marketing